Mediating effects of sleep duration on the association between natural menopause and stroke risk among Chinese women - Liu, Xingyue; Zhang, Juhua; Peng, Shuzhi; Pei, Mengyun; Dai, Chunying; Wang, Tingting; Zhang, Peng (Frontiers in Neuroscience, 2022)
Background: Sleep disturbance is commonly reported by menopausal women. Stroke risk and poor stroke outcomes in women have usually been attributed to menopause. This study aimed to investigate the mediating effect of sleep duration on relationship between menopause and risk of stroke in natural menopause women. Methods: A cross-sectional study was executed, and participants were recruited through a multistage, stratified, probability proportional to size sampling method in this research. The stroke risk was measured using the risk assessment form for high-risk stroke population. The average sleep duration was calculated by adding up night sleep and afternoon nap duration. Multivariate regression analysis was conducted to identify the association between menopause, sleep duration, and stroke risk. The direct and indirect effects of menopause on stroke risk were analyzed by using the sleep duration in a mediation framework. Results: Menopause (β = 2.450, 95%CI: 2.181 ~ 2.718; β = 2.443, 95%CI: 2.174 ~ 2.712; β = 2.917, 95%CI: 2.678 ~ 3.155, P＜0.001), average sleep duration (β = -0.281, 95%CI: -0.351 ~ -0.211, P＜0.001), night sleep duration (β = -0.332, 95%CI: -0.405 ~ -0.260, P＜0.001), afternoon nap (β = 0.159, 95%CI:0.014 ~ 0.304, P＜0.032) and stroke risk were significantly associated, after adjusting for covariates. Menopause was significantly related to average sleep duration (β = -0.142, P＜0.001) and night sleep duration (β = -0.148, P＜0.026). The average sleep duration (indirect effect ab = 0.027, 95%CI: 0.016~0.041) partially mediated the relationship between menopause and stroke risk, in which the night sleep duration (indirect effect ab = 0.034, 95% CI: 0.022~0.047) played a major mediating role. Conclusion: A significant relationship between menopause and stroke risk factors among natural menopause was found in this study. The average sleep duration, especially night sleep duration, partially mediated the association between menopause and stroke risk, which is a novel insight to the progression of stroke risk in Women. Suitable prevention methods and interventions for sleep in menopausal women may reduce the risk of stroke.